New Hasselblad center - Caseva, Felix; Nilsson, Viktor (My University, 2025)
This thesis has investigated how Hasselblad’s historical heritage and distinctive design language can be translated into an architectural expression for a new Hasselblad Center in Gothenburg. Rooted in the city where Hasselblad cameras were first designed and manufactured, the project responds to the Hasselblad Foundation’s need for dedicated exhibition galleries, research facilities, public amenities, and a venue for its prestigious awards ceremony. The ambition has been to honour Hasselblad’s cultural significance, clarify the Foundation’s dual commitment to photography and the natural sciences, and enrich Gothenburg with a landmark institution. Iterative cycles of traditional drawings, digital and physical models, and visualisations have been used in the study with a research-by-design methodology. Charles Felix Lindberg’s Plats was identified by site analysis as an underutilised urban node that is close to both public green space and major streets. Volume studies and early explorations abstracted key camera components— the circular lens, the cuboid body, and the modular film back— into elemental forms. Interviews with Foundation stakeholders and scientists, excursions to pertinent projects, and literature studies on embodied experience informed programmatic requirements and spatial strategies. The resulting design features a circular courtyard—invoking the camera lens—as an accessible “oasis” that mediates between Avenyn’s grandeur and the intimate interior. Inspired by the modularity of the 500C, the underground galleries with a flexible exhibition wall system enable reconfiguration and colour change without wasting material. A research library, a photographic archive, offices, an auditorium, a restaurant, and a café are unified within a coherent composition of spaces evoking an abstracted 500C camera. Researcher workspaces flank public circulation, visually expressing the Foundation’s scientific mission. This thesis has demonstrated how heritage can be abstracted into architectural form to create a facility that is both expressive and operationally sound. By integrating theoretical insights on sensory experience and stakeholder needs, the new Hasselblad Center emerges as a project in aligning institutional identity with spatial experience—offering a study for future museum projects seeking to embody their unique legacies.